1989
DOI: 10.1007/bf01401339
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime measurement of some levels belonging to 3p 4 4p configuration of Ar II

Abstract: High frequency deflection technique with delayed coincidence single photon counting arrangement has been used to measure the lifetimes of some excited states of argon II. The measurements have been performed under conditions where pressure-dependent effect is negligible. The instrumental response function has been obtained directly and the measured decay curves have been deconvoluted using this response function to yield the lifetimes of the levels concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Of special importance is the analysis of the following levels: (1) 139 094 cm −1 , the value of Blagoev et al is τ < 3 ns, in very well accordance with the theoretical calculations, whereas Das and Bhattarchaya gives 6 ns. Because these authors have an equipment with a time resolution of nearly 3 ns, as indicated in a previous article about the levels of Ar II [21], they cannot measure very short lifetimes. Moreover, the line with a wavenumber of 139 094 cm −1 is observed in the VUV spectra [1] and because the transition probability depends on σ 3 , that line determines basically the lifetime.…”
Section: Results and Tablesmentioning
confidence: 97%
“…Of special importance is the analysis of the following levels: (1) 139 094 cm −1 , the value of Blagoev et al is τ < 3 ns, in very well accordance with the theoretical calculations, whereas Das and Bhattarchaya gives 6 ns. Because these authors have an equipment with a time resolution of nearly 3 ns, as indicated in a previous article about the levels of Ar II [21], they cannot measure very short lifetimes. Moreover, the line with a wavenumber of 139 094 cm −1 is observed in the VUV spectra [1] and because the transition probability depends on σ 3 , that line determines basically the lifetime.…”
Section: Results and Tablesmentioning
confidence: 97%
“…Details concerning the experimental set-up were reported previously [8,9]. A pulsed beam of high energy electrons (4 keV) was used to excite the atoms to the levels of interest, the DC beam current being 2 mA.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Here the experimental set up is the same as used previously [2], the only difference is that here a condensing lens (Oriel 77260 lens-filter-shutter assembly) has been used for focusing the emitted radiation exactly onto the monochromator entrance slit. This causes an enhancement in intensity of the emitted spectral line and hence increases the spectral resolution that reduces the problem of line blending.…”
Section: Methodsmentioning
confidence: 99%